Spanish Seamen's Strike : inter-departmental correspondence - Tewson, Vincent
001-0196-001 TRADES UNION CONGRESS GENERAL COUNCIL INTER-DEPARTMENTAL CORRESPONDENCE. From. H.V.Tewson Department 8th July 1936 To Mr. Bolton. Date Secretary's. SUBJECT. SPANISH SEAMEN'S STRIKE. The attached file contains letters we have received in regard to the above matter. The last one from the Aberdeen Trades Council I have not replied to. Do you think you could get an opportunity of speaking to Cabellero on the matter? 292/946/1/196